Analisis Tingkat Seismisitas dan Percepatan Tanah Maksimum (PGA) Wilayah Sulawesi Tenggara Berdasarkan Data Gempabumi Periode 1973-2022 - Al Rubaiyn; Jamhir Safani; Khairul Anwar (Program Studi Teknik Geofisika FITK UHO, 2023)
Abstract. An analysis of seismicity level and maximum ground acceleration of Southeast Sulawesi region has been conducted. The purpose of this research is to map the level of rock fragility (b value), seismicity level (a value), and maximum ground acceleration (PGA) of Southeast Sulawesi. The earthquake data used is sourced from USGS and BMKG for the period 1973-2022. Zmap software was used to calculate a value and b value. PGA from accelerograph data was used to find a suitable empirical method to calculate the PGA of Southeast Sulawesi. The selection of a suitable method is based on the smallest average error value. Based on the analysis results obtained, the value of rock fragility level ranges from 0.355-1.337 while the seismicity level ranges from 2.773-7.879 with the highest value is in the southeast area of Southeast Sulawesi. The comparison results of PGA values from accelerograph data and empirical methods show that the Liu & Tsai method has the lowest RMSE of 5.27 gal. Liu & Tsai's PGA values for Southeast Sulawesi ranged from 18.6-155.7 gal.